2015
DOI: 10.1007/s11837-015-1644-9
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Stability and Grain Boundary Complexion Formation in a Nanocrystalline Cu-Zr Alloy

Abstract: Nanocrystalline Cu-3 at.% Zr powders with ~20 nm average grain size were created with mechanical alloying and their thermal stability was studied from 550-950 °C. Annealing drove Zr segregation to the grain boundaries, which led to the formation of amorphous intergranular complexions at higher temperatures. Grain growth was retarded significantly, with 1 week of annealing at 950 °C, or 98% of the solidus temperature, only leading to coarsening of the average grain size to 54 nm. The enhanced thermal stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
89
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 80 publications
13
89
2
1
Order By: Relevance
“…These values are also provided for comparison in Table 1. The lack of rampant grain growth was at least partially the result of AIF formation and not solely resulting from the existence of secondary phases, as the amount of ZrC present in the sample is not enough to limit grain growth through Zener pinning [36] and X-ray and electron diffraction confirmed that no intermetallics phases were present. We do note that the carbide particles do aid the thermal stability of the alloys, with the ZrC particles and AIFs likely being complementary features for this alloy.…”
mentioning
confidence: 95%
“…These values are also provided for comparison in Table 1. The lack of rampant grain growth was at least partially the result of AIF formation and not solely resulting from the existence of secondary phases, as the amount of ZrC present in the sample is not enough to limit grain growth through Zener pinning [36] and X-ray and electron diffraction confirmed that no intermetallics phases were present. We do note that the carbide particles do aid the thermal stability of the alloys, with the ZrC particles and AIFs likely being complementary features for this alloy.…”
mentioning
confidence: 95%
“…Past studies have shown that AIFs tend to form at grain boundaries with high relative solute excess [58]. Since high energy grain boundaries may accommodate more solute segregation [59,60], and ball-milled nanocrystalline metals have been shown to have a higher grain boundary energy than a fully-equilibrated high angle grain boundary [61], it is expected (and has been confirmed multiple times [34,56,62]) that AIFs can readily form in this ball milled nanocrystalline alloy.…”
Section: Methodsmentioning
confidence: 68%
“…Even for the ordered grain boundary samples, it is worth noting that the thermal input alone is not sufficient to cause any of the observed grain growth. Annealing studies of the same ballmilled nanocrystalline Cu-Zr alloy showed excellent thermal stability at 750 °C even when ordered grain boundaries still dominated the grain boundary network [34] due to the combined effects of Zr dopant segregation that lowers the grain boundary energy and kinetic pinning from ZrC particles. It is also important to note that the ZrC particles and AIF thicknesses may also have been altered by irradiation which would in turn impact subsequent radiation tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic stabilization generally involves alteration of the grain boundary mobility through solute drag and Zener pinning caused by particle dispersions [32][33][34][35][36][37][38], which has been observed for Cu-Ta [38,39] and Cu-Nb [40]. Thermodynamic stabilization methods seek to reduce the root driving force for grain growth by reducing the grain boundary energy through dopant segregation to the grain boundary region [23,24,26,27,[41][42][43][44], which has been observed for a variety of systems including Ni-W [45], W-Ti [46], Fe-Zr [47], and Cu-Zr [48]. [49] recently reviewed how dopant segregation can be used to tailor thin film microstructures for a multitude of alloys, including Fe-Pt [50], Cu-Ni [51], Fe-Cr [52], and W-Ti [53].…”
Section: Graphical Abstractmentioning
confidence: 99%
“…Cu-Nb as a thin film was instead structurally altered by the formation and growth of dewetted Cu particles, where the dewetted particles increased in number and size with increasing temperature. Ball milled Cu-Zr has been found to remain nanostructured even after a week at 98% of its solidus temperature [48], which was primarily attributed to thermodynamic stabilization caused by dopant segregation and grain boundary complexion transformations. Instead of a thermodynamically stabilized material, the thin Cu-5Zr film collapsed into large dewetted Cu particles.…”
Section: ) Formentioning
confidence: 99%